RESISTING SOCIAL CONSTRUCTION OF WOMANHOOD: A PSYCHOANALYTIC READING OF PORTIA’S GENDER CONSTRUCTION IN ELIZABETH BOWEN’S THE DEATH OF THE HEART - Melania Priska Mendrofa (STBA Prayoga Padang, 2018)
This paper aims to analyze Portia‟s resistance toward social construction of womanhood. Portia's subjectivity is constructed by mother-daughter's unity that stimulates Portia's dependency on her mother's figure. Since she becomes a lacking subject of knowledge and experience toward social life, she is supposed to separate herself from maternal attachment and to shift her life to the symbolic father in order to be an autonomous figure. Meanwhile, the symbolic father sets symbolic language that is the language used by society that constructs feminine identity for the daughter and triggers forbidden pleasure. Thus to resist the social construction of womanhood, sisterhood is needed. Inter-subjective dialogue between women helps them to escape from male‟s dictation or oppression. It does not only provide the experience of nurturance but also ability to control and manage their own identity.